Influence of fracture parameters on hydraulic shear seepage characteristics of granite - Jupeng Tang; Honghao Yu; Zhihao Wei; Xiao Zhang (Case Studies in Thermal Engineering, 2024)
To reveal the influence mechanism of different fracture parameters on the permeability characteristics of hot dry rock after hydraulic shear. The self-made high temperature true triaxial hydraulic shear test device and rock roughness profile tester were used. The granite in Daqing area of Songliao Basin is taken as the research object. The prefabricated fractured granite is subjected to high-temperature treatment. The geological characteristics of different geothermal reservoirs are simulated by changing the three-dimensional stress. The roughness coefficient of the fracture surface is used to characterize the variation characteristics of fracture before and after hydraulic shear. The influence of different fracture angles and roughness on the permeability of granite after hydraulic shear was tested. Combined with numerical simulation, the relationship between fracture parameters and geothermal mining performance is analyzed. The results show that the maximum water injection pressure of hydraulic shear decreases with the increase of fracture angle by quadratic polynomial law and increases with the increase of fracture roughness by quadratic polynomial law. The variation of fracture surface roughness coefficient fluctuates within 0–2 with the increase of volume stress before and after hydraulic shearing. The variation of fracture surface roughness coefficient increases linearly with the increase of water injection flow rate and increases with the increase of water injection time, and there is a fluctuation range of 0.38–0.44. After hydraulic shear, the permeability of granite increases first and then decreases with the increase of fracture angle. When the fracture angle is 15°, the permeability has the maximum value. The permeability increases with the increase of fracture surface roughness. The numerical simulation results show that the high fracture opening (15 mm), high fracture number, and high fracture penetration performance significantly improve the geothermal mining efficiency.